Compositional study of mixed halide perovskite films CH3NH3Pb(I1-xBrx)3 and CH3NH3Pb(I1-xClx)3 prepared by close space sublimation. (December 2020) - Pérez-Gutiérrez, Enrique; Percino, M. Judith; Santos, Pilar; Cerón, Margarita; Ceballos, Paulina; Montoya, Diana Marcela; Barbosa-García, Oracio; Thamotharan, Subbiah
Graphical abstract: Abstract: The preparation and characterization of homogeneous and crystalline films of the perovskites CH3 NH3 Pb(I1- x Br x )3 and CH3 NH3 Pb(I1- x Cl x )3 obtained by the close space sublimation method are reported. Perovskites with a mixture of halides were prepared by the sublimation of the methylamine halide CH3 NH3 Br or CH3 NH3 Cl over predeposited lead iodide films at different sublimation times to modify the I:Br or I:Cl ratio. The perovskite films CH3 NH3 Pb(I1- x Br x )3 showed a bandgap shift. For CH3 NH3 Pb(I1- x Cl x )3 films with sublimation times of 2.5−40 min, no changes were observed; however, for longer times, the absorption spectrum became similar to that of the CH3 NH3 PbCl3 material. In this study, the mixed halide perovskites CH3 NH3 Pb(I1- x Br x )3 and CH3 NH3 Pb(I1- x Cl x )3 were prepared with just two precursors, instead of the common approaches that use PbI2, PbBr2, MAI and MABr, as well as PbI2, PbCl2, MAI and MACl. Perovskite layers were applied for the fabrication of solar cell devices, and efficiencies of 9.9 % and 10.2 % were achieved for CH3 NH3 Pb(I1- x Br x )3 and CH3 NH3 Pb(I1- x Cl x )3, respectively. In addition, perovskite LEDs were also prepared. While the well-known green emission at 533 nm was observed for CH3 NH3 Pb(I1- x Br x )3, for the CH3 NH3 Pb(I1- x Cl x )3 based-devices, a broad emission spectrum similar to a warm white emission was obtained. Therefore, a new approach through the sublimation method is reported to fabricate solar cells and LEDs where the main parameter to regard is the sublimation time.